EVALUACIÓN DEL pH EN CANALES DE TOROS HOLSTEIN (Bos taurus) Y NELORE (Bos indicus) - Mariño A., Gino (2005)
With the objective to find differences racial, the curve of variation of pH of the meat in 50 bulls Holstein (Bos taurus) and 50 bulls Nelore (Bos indicus) was determined, with ages between 12-24 months The pH measurements was taken in the Longissimus dorsi muscle after 1, 2, 3, 4, 5, 6, 8, 10, 12, 15, 18, 24 hours post mortem. Data was submitted to regression analysis. The pH values were expressed through a cubic regression equation,(in Holstein cattle w = 7.107273 – 0.314504x + 0.019409x2 – 0.000374x3 with R2 = 0.814 and in Nelore was w = 7.005286 – 0.309965x + 0.019198x2 – 0.00378x3 with R2 = 0.767). those of the Holstein race were slightly greater to those of the Nelore race, presenting racial differences (p< 00.5), however in both races they follow similar tendency during the first 24 h post mortem and reach an suitable degree of acidity to inhibit the microbial growth and to promote a good meat quality.